Spectrum of Haemoglobinopathies in a Tertiary Care Hospital of Armed Forces - Chopra, GS (Med J Armed Forces India, 2008)
BACKGROUND: Thalassaemia and other structural haemoglobinopathies are the major genetic disorders prevalent in certain parts of the world including India. This study presents the pattern of haemoglobinopathies amongst the referred patients of anaemia in a two-year period. METHODS: A total of 1032 patients were studied during a two-year period for anaemia investigation. Haematological indices, sickling test and haemoglobin electrophoresis with quantification of the bands was done in all cases. RESULT: Out of 1032 cases, 774 (75%) were normal and 258 (25%) cases had abnormal haemoglobin pattern. Of the 258 abnormal cases, 136 (53%) were males and 122 (47%) were females. Of all cases of anaemia 370 (36%) were microcytic hypochromic, 237 (23%) macrocytic, 151 (15%) were dimorphic and the rest (26%) had normocytic normochromic picture. 82% of microcytic hypochromic anaemias had reduced serum iron and elevated total iron binding capacity (TIBC), whereas 85% had decreased serum ferritin levels. Spectrum of haemoglobinopathies prevalent were β-Thalassemia trait (17%), followed by sickle cell trait (2.3%). Other haemoglobinopathies in descending order of frequency were sickle cell disease (1.7%), Hb D trait (1%), Hb E trait (0.8%), sickle cell – β thalassemia, Hb E disease, E – β thalassemia (0.6% each) and thalassemia major (0.4%). CONCLUSION: This study provides a comprehensive database on the spectrum of haemoglobinopathies in the Armed Forces. It is suggested that detection of HbA(2) should be carried out in all the high-risk groups with anaemia.